Redefining QRS transition to confirm left bundle branch capture during left bundle branch area pacing - Briongos-Figuero, Sem; Estévez Paniagua, Álvaro; Sánchez Hernández, Ana; Muñoz-Aguilera, Roberto (Frontiers in Cardiovascular Medicine, 2023)
Sem Briongos-Figuero has contributed to the conception, design and acquisition of data.He has drafted the work and reviewed it. He provided approval for publication and agreed to be accountable for all aspects of the work.Álvaro Estévez-Paniagua has contributed to the conception, design and acquisition of data. He has drafted the work and reviewed it. He provided approval for publication and agreed to be accountable for all aspects of the work.Ana Sánchez Hernández has contributed to the acquisition of data. She has reviewed it. She provided approval for publication and agreed to be accountable for all aspects of the work.Roberto Muñoz-Aguilera has contributed to the acquisition of data. He has reviewed it.He provided approval for publication and agreed to be accountable for all aspects of the work.